Review of nonlinear oscillatory shear flow notations and presentations: polymeric liquids. (October 2019) - Saengow, C.; Giacomin, A.J.
Abstract: We review notations for, along with ways of presenting, the shear stress responses to large-amplitude oscillatory shear flow (LAOS). We find that the Fourier loss and storage viscosities to be the simplest primal notations for interpreting LAOS. The relative intensities provide the best evidence for oscillatory shear entering the large-amplitude regime. Deviation from linear viscoelastic behaviors can be observed through the distortions of Lissajous loops. We explore these loops in their elastic and viscous projections. The centerpiece of this work is our review table, which summarizes experimental measurements for polymer melts and solutions, targeting 21st century publications. Our review also provides conversion formulae to go from any of many notations to the Fourier loss and storage viscosities. The review table also defines which part of the LAOS measurement field has yet to be ploughed and shines light on which notations have been used, and for which purposes, to interpret nonlinearities. Graphical abstract: Image 1